ORGANOGENESIS TANAMAN GAHARU (Aquilaria malaccensis Lamk) PADA BERBAGAI KONSENTRASI ZAT PENGATUR TUMBUH Benzyl Amino Purin (BAP) - Indole Butiric Acid (IBA) SECARA IN-VITRO - A, Arhvitasari; m, Muslimin; w, Waeniyanti; w, wardah (Jurnal Warta Rimba, 2019)
Agarwood (Aquilaria malaccensis Lamk) is one type of forestry plant that has been developed with tissue culture techniques. The provision of growth regulators can be done by adding in the growing media used. Growth regulators used are usually in the form of auxins and cytokines. This study aims to obtain the concentration of growth regulators with the combination of Benzyl Amino Purine (BAP) -Indole Butyric Acid (IBA) which is the best for organogenesis of aloe plants (Aquilaria Malaccensis Lamk) in vitro. This study uses a completely randomized design (CRD) method consisting of 5 BAP-IBA combination treatments namely V0 = MS0 (control), V1 = MS + 0.8ppm BAP + 0.1ppm IBA, V2 = MS + 1.0ppm BAP + 0 , 1ppm IBA, V3 = MS + 1.5ppm BAP + 0.1ppm IBA, V4 = MS + 2.0ppm BAP + 0.1ppm IBA. The parameters observed in this study were the initial emergence of shoots, the number of shoots, and a number of leaves. The Smallest Significant Difference (BNT) test was carried out if the analysis of variance showed that the BAP-IBA combination treatment had a significant effect. The results showed that the combination of BAP-IBA on various treatments that were tried had a very significant effect on the initial emergence of shoots, a number of shoots and a number of leaves. The best treatment was found in V1 with MS concentration + 0.8ppm BAP + 0.1ppm IBA was able to induce early formation of the fastest buds with an average of 5.00 days after planting (HST), the highest number of shoots with an average of 3.00 shots, the highest average number of leaves is 1.80 strands, and the highest growth percentage is 100.00%.